Lista propuesta de anfibios y reptiles amenazados de extinción - Bertonatti, Claudio (1994)
A preliminary list on endangered amphibians and reptiles of Argentina is presented. On the basis of published and unpublished information, and following the UICN criteria, 123 of 370 herp species were categorized.